Total dose and displacement damage effects in a radiation-hardened CMOS APS. - Bogaerts, J. (IEEE Transactions on electron devices)
A 512×512 CMOS active pixel sensor (APS) was designed and fabricated in a standard 0.5-μm technology. The radiation tolerance of the sensor has been evaluated with Co-60 and proton irradiation with proton energies ranging from 11.7 to 59 MeV. The most pronounced radiation effect is the increase of the dark current. However, the total ionizing dose-induced dark current increase is orders of magnitude smaller than in standard devices. It behaves logarithmically with dose and anneals at room temperature. The dark current increase due to proton displacement damage is explained in terms of the nonionizing energy loss of the protons. The fixed pattern noise does not increase with total ionizing dose. Responsivity changes are observed after Co-60 and proton irradiation, but a definitive cause has not yet been established.